EKSPLORASI, ISOLASI DAN SELEKSI JAMUR ENTOMOPATOGEN PLUTELLA XYLOSTELLA (LEPIDOPTERA: YPONOMEUTIDAE) PADA PERTANAMAN CAISIN (BRASSICA CHINENSIS) DI SUMATERA SELATAN - Haperidah Nunilahwati; Siti Herlinda; Chandra Irsan; Yulia Pujiastuti (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2012)
Plutella xylostella is the most destructive insect pests of the brassicae family. The research objective was to explore, isolate and select entomopathogenic fungi as biological agents for control of P. xylostella. This study used 20 fungal isolates originating from soil and infected insects around the farmers’ field in lowland and highland of South Sumatra. The fungal isolates were tested to third instar larvae of P.xylostella. The suspension of entomopathogenic fungus was topical inoculated with a density of 1x106 conidia ml-1 on the test insect and five replicates. The result showed that the highest (83%) and the lowest (41%) mortality of the larvae P.xylostella was induced by fungal BPluS and BNIPTr, respectively. Moreover, the shortest (2.1 days) and the highest (4.3days) lethal times of the infected host were induced by fungal BPluS and BNIPTr, respectively.